A sustainable approach towards the three-component synthesis of unsubstituted 1H-imidazoles in the water at ambient conditions. Issue 7 (28th June 2021) - Kapale, Suraj S.; Chaudhari, Hemchandra K.; Mali, Suraj N.; Takale, Balaram S.; Pawar, Hitesh
Abstract: A green protocol for the synthesis of unsubstituted imidazoles has been demonstrated herein. The reaction is realized using commercially available lipase enzyme, porcine pancreas lipase (PPL) in water. The reaction conditions are selective and mild which helped to tolerate a wide variety of functional groups to give the desired products in good chemical yields.